Satire in the Victorian novel - Russell, Frances Theresa, 1873-1936 (Salt Lake City, UT : Project Gutenberg, 2022)
"Satire in the Victorian Novel" by Frances Theresa Russell is a scholarly publication written in the early 20th century. This work examines the intersection of satire and the English novel during the Victorian era, emphasizing the critical role of satire as a literary form. The author likely analyzes various Victorian novelists and their satirical techniques, elaborating on how their works reflect social and moral critiques of their time, engaging deeply with the complexities of human folly and deception. At the start of the book, Russell introduces the concept of satire, discussing its ambiguous reception and its dual nature as humor and criticism. She reflects on the challenges satirists face in understanding and portraying their subjects, particularly in a society rife with deception and pretense. By exploring the historical context of Victorian literature, Russell sets the stage for examining key authors and their satirical contributions, hinting at the depth and breadth of this literary genre and its significant impact on society. Overall, the opening portion serves as an invitation to delve deeper into the intricate relationships between satire, fiction, and the prevailing social ethos of Victorian England. (This is an automatically generated summary.)
Release date is 2022-03-07
Charlene Taylor, Karin Spence and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Thesis (Ph. D.); Satire, English -- History and criticism; English fiction -- 19th century -- History and criticism